The urinary calcium/creatinine ratio as a measure of urinary calcium excretion - Wills, M. R. (1969)
Urine specimens were collected from 26 normal subjects, 10 patients with proven primary hyperparathyroidism, and eight patients with hypercalcaemia due to other causes. After overnight urine concentration, an oral water load was given to induce a diuresis and provide urine specimens with a relatively wide range of creatinine concentration for each subject. In normal subjects the urinary calcium/creatinine ratio was found to be independent of urine concentration. In eight out of 10 patients with primary hyperparathyroidism and in two out of eight patients with hyper-calcaemia due to other causes, the urinary calcium/creatinine ratio was found to be high when the creatinine concentration was low, but usually normal when the creatinine concentration was high. The results suggest that if the urinary calcium/creatinine ratio of random urine specimens is used as a `screening' procedure to detect hypercalciuria the latter cannot be excluded if the urinary creatinine concentration is more than 40 mg per 100 ml.